Study on the protective effect of green tea against bisphenol A- induced amyloid aggregation in the brain of male albino rats. - Dhuha Q. Kamil; Khabat A. Ali (Zanco Journal of Pure and Applied Sciences, 2020)
Bisphenol A (BPA) has been used in the plastic industry and widely distributed in the environment. Green tea extract has been known for its antioxidant activity. This study was designed to investigate the protective efficacy of green tea against brain amyloid aggregation which induced by BPA. Twenty male albino rats were exposed to BPA (500 mg/kg); green tea ethanolic extracts in two dose levels 150 and 300 mg/kg respectively plus BPA. After 60 days, malondialdehyde (MDA), superoxide dismutase (SOD) in the brain were measured besides body and brain weights. BPA exposed groups showed a significant reduction (P<0.05) in the final body weight, with a non-significant reduction in absolute brain weight. BPA was also increased oxidative stress in the brain of the treated rats besides histological changes with amyloid deposition in the brain detected by congo red staining technique. Treatment with green tea ethanol extracts were protected animal brains against adverse effects caused by BPA and reduced oxidative stress in a dose-dependent manner. that may be related to enriched ingredients that have been found in the extract.